HETEROSIS AND COMBINING ABILITY FOR EARLINESS AND ITS RELARELATED TRAITS IN COTTON (GOSSYPIUM HIRSUTUM L.) - H. V. SOLANKI; D. R. MEHTA; V. B. RATHOD; P. A. VAVDIYA (The Bioscan, 2015)
A line x tester mating design comprises 10 lines and 5 testers of Gossypium hirsutum indicated preponderance of additive and non-additive gene action for days to 50% flowering, days to 50% boll brusting and seed cotton yield per plant respectively. Parent 76 IH 20 were the best general combiners to 50% flowering (-6.133), days to 50% boll brusting (-6.087) and seed cotton yield per plant (11.861). Crosses G.cot-12 x MR 786 for days to 50% flowering (-10.27); LRA 5166 x GJHV 503 (-9.65) and G.cot-12 x H 1316 (-6.78) for days to 50% boll brusting were the best specific combinations to exploit non-fixable components. The gca effects for all the traits indicated more or less similar trend in per se performance. Hence, parents having lower mean performance for days to 50 % flowering could be selected for exploiting earliness in cotton hybrids.